Mechanical Properties of Hybrid Carbon Fibers Reinforced Modified Foamed Concrete - Njyman, Areej; Hilal, Ameer A (Iraqi Journal of Civil Engineering, 2025)
Foamed concrete (FC) is a type of lightweight concrete characterized by a high void space ratio and cementitious binders. In this research, the fresh and mechanical properties of fiber-reinforced modified foamed concrete (made with fly ash, silica fume, and superplasticizer) with a density of 1300 kg/m³ were studied. Carbon fibers of different lengths (12 mm, 20 mm, and 28 mm) were introduced in two ways: as single fibers (12 mm) and as hybrid fibers combining lengths of 20 mm and 28 mm. The results showed that the compressive and split tensile strengths increased by approximately 43% compared to the control mix (modified with additives) when using a single fiber of 12 mm at a volume proportion of 0.4%. In contrast, using hybrid fibers resulted in increases of about 65% and 66% in compressive and split tensile strengths, respectively. When compared to the single fiber method, the hybrid approach improved compressive and split tensile strengths by about 15% and 16%, respectively.